Development of a practice tool for community-based nurses: The Heart Failure Palliative Approach to Care (HeFPAC). (April 2014) - Strachan, Patricia H; Joy, Cathy; Costigan, Jeannine; Carter, Nancy
Background: Patients living with advanced heart failure (HF) require a palliative approach to reduce suffering. Nurses have described significant knowledge gaps about the disease-specific palliative care (PC) needs of these patients. An intervention is required to facilitate appropriate end-of-life care for HF patients. Aims: The purpose of this study was to develop a user-friendly, evidence-informed HF-specific practice tool for community-based nurses to facilitate care and communication regarding a palliative approach to HF care. Methods: Guided by the Knowledge to Action framework, we identified key HF-specific issues related to advanced HF care provision within the context of a palliative approach to care. Informed by current evidence and subsequent iterative consultation with community-based and specialist PC and HF nurses, a pocket guide tool for community-based nurses was created. Results: We developed the Heart Failure Palliative Approach to Care (HeFPAC) pocket guide to promote communication and a palliative approach to care for HF patients. The HeFPAC has potential to improve the quality of care and experiences for patients with advanced HF. It will be piloted in community-based practice and in a continuing education program for nurses. Conclusion: The HeFPAC pocket guide offers PC nurses a concise, evidence-informed and practical point-of care tool to communicate with other clinicians and patients about key HF issues that are associated with improving disease-specific HF palliative care and the quality of life of patients and their families. Pilot testing will offer insight as to its utility and potential for modification for national and international use.